ETIOLOGY AND PATHOGENESIS OF HYPERTROPHIC GINGIVITIS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Hypertrophic gingivitis is a common inflammatory periodontal condition characterized by an abnormal enlargement of gingival tissues. The disease is frequently observed in adolescents, pregnant women, and patients with poor oral hygiene or systemic conditions that influence periodontal health. The aim of this study was to analyze the etiological factors and pathogenic mechanisms responsible for the development of hypertrophic gingivitis. A review of scientific literature published between 2000 and 2025 was conducted using medical databases including PubMed, Scopus, and Google Scholar. The results indicate that hypertrophic gingivitis develops due to a combination of local and systemic factors such as dental plaque accumulation, hormonal changes, certain medications, and systemic diseases. Persistent inflammation stimulates excessive proliferation of connective tissue and epithelium, leading to gingival enlargement. Early diagnosis and elimination of etiological factors are essential for effective treatment and prevention of disease progression.